To escape or to pursue: opposite decision making concerning a single moving object is influenced by starvation and sex - Salido, Carla Adriana (2023)
Decision-making processes in the context of prey-predator interactions are studied from the side of the prey or the predator. Thus, prey capture and escape behaviours are researched separately, using different stimuli in different species. The crab Neohelice preys upon individuals of its own species; hence, it behaves as prey and as predator. These two innate opposite behaviours can be elicited by the same object moving on the ground. Here, we studied how the decision to perform avoidance, predatory or freezing responses to a moving dummy depends on sex and starvation level. In the first experiment, we assessed the probability of each response type in unfed crabs for 22 days. Males showed a higher predatory response probability than females. When starvation increased, the predatory response increased, while avoidance and freezing declined, but this only occurred in males. In the second experiment, we compared regularly fed and unfed males for 17 days. While fed crabs did not change their behaviour throughout the experiment, unfed crabs significantly intensified their predatory responses, displayed different exploratory activities and pursued earlier than fed crabs. Our results show the unusual situation of an animal that, to deal with a single stimulus, has to choose between opposite innate behaviours. This is a value-based decision as it is affected by factors other than the stimulus itself.